KONTRIBUSI KOMPONEN FISIK TERHADAP KEMAMPUAN BANTINGAN PINGGANG PADA OLAHRAGA GULAT MAHASISWA YPUP MAKASSAR - Yusuf, Akbar (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi STKIP Mega Rezky Makassar, 2018)
This study aims to determine the contribution of physical components in doing waist straps on the sport wrestling student YPUP Makassar. the research method used is descriptive with the sample research of 50 students. the results of this study indicate the contribution of limb strength to the ability of waist straps and the elasticity of the ability of waist straps as well as the contribution of limb strength and the elasticity of the waist-knee capability in the student wrestling sport YPUP Makassar